ANALISIS PERKEMBANGAN SEKTOR INDUSTRI TERHADAP PEREKONOMIAN INDONESIA - Nadia Dwi Agustin; Syifa Nia Agustin; Gustina Masitoh (Universitas KH. Mukhtar Syafaat, 2026)
This study aims to analyze the development of the industrial sector and its contribution to the Indonesian economy. In addition, this research examines the factors influencing the development of the industrial sector and its impact on economic growth. The industrial sector plays a strategic role in driving economic growth through value creation, increased productivity, and employment generation. This study employs a qualitative approach using descriptive analysis based on secondary data from various official sources. The results show that the industrial sector in Indonesia has experienced significant development in recent years and has made a substantial contribution to the national economy. This development is influenced by several factors, including the quality of human resources, technological advancement, and government policies. Furthermore, the industrial sector has a positive impact on economic growth by increasing public income and overall economic activity. Therefore, appropriate strategies are needed to enhance the competitiveness of the industrial sector in order to support sustainable economic growth. Keywords:Industrial Sector, Economic Growth, Economic Contribution, Industrial Development